Syntactic and semantic coherence in Negative Polarity Items (NP1)-triggering; evidence from Dutch and Afrikaans - ter Horst, Paul (SA journal of linguistics = SA tydskrif vir taalkunde, 1999)
The aim of this article is to gain a clearer understanding of the contexts in which negative polarity items are found & why they are found in these contexts. First I explain what negative polarity items are & what kind of context they require. Next I introduce two different ways of classifying negative polarity items, by grammatical & semantic criteria. I then present my own research, in which I compared Dutch negative polarity items & their Afrikaans counterparts. In order to see whether there is a match between the grammatical & the semantic classification of negative polarity items, negative polarity items of different grammatical & semantic classes are considered. My conclusion is that there is a causal relation between the semantic & the grammatical classification. 3 Tables, 5 Figures, 11 References. Adapted from the source document